L’Age des tenebres 2.0 : L’Humanite au nadir dans Serotonine de Michel Houellebecq et Die troebel tyd d’Ingrid Winterbach - Du Plooy, Jacobus Andrias (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.